DIGITAL ACCOUNTING SYSTEM EFFECTIVENESS (DASE) AND DIGITAL ACCOUNTING SYSTEM SUCCESS (DASS) AND CORPORATE GOVERNANCE (CG): A STRUCTURAL EQUATION MODELING APPROACH IN THE HOSPITALITY INDUSTRY - Fahry Reza; Beni Ismarizal; Djenni Sasmita; Indah Noviyanti; Novita Herlissha; M. Aries Farhan (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study aims to examine the effect of Digital Accounting System Effectiveness (DASE) and Digital Accounting System Success (DASS) on Corporate Governance (CG) in the hospitality industry in Indonesia. Research Methodology: This research was conducted in the hospitality industry (hotels) in Indonesia using a quantitative approach. Data were collected through a structured questionnaire distributed to 200 respondents consisting of hotel managers, accounting/finance staff, and operational employees who use Digital Accounting Systems (DAS). The study employed a cross-sectional survey design. Data analysis was conducted using PLS-SEM. Results: The results show that budgeting system, system quality, information quality, and service quality have a positive and significant effect on corporate governance. Among these variables, service quality is the most dominant factor in improving corporate governance. In contrast, bookkeeping system, AIS security, and IFRS adoption do not have a significant effect on corporate governance in the hospitality context. Conclusions: The study concludes that improvements in corporate governance are more strongly driven by system performance aspects, information quality, service quality, and budgeting practices rather than formal accounting compliance factors. Limitations: The limitations of this study include its focus on the Indonesian hospitality industry and the use of a cross-sectional design, which does not capture changes over time. In addition, the use of self-reported questionnaire data may introduce subjective bias. Contributions: This research contributes to the literature on digital accounting systems and corporate governance by integrating DASE and DASS in the hospitality context. It provides practical implications for hotel managers and policymakers in enhancing corporate governance through improved system quality, information quality, service quality, and budgeting practices.